2022
DOI: 10.1038/s42003-022-03308-w
|View full text |Cite
|
Sign up to set email alerts
|

Wuschel2 enables highly efficient CRISPR/Cas-targeted genome editing during rapid de novo shoot regeneration in sorghum

Abstract: For many important crops including sorghum, use of CRISPR/Cas technology is limited not only by the delivery of the gene-modification components into a plant cell, but also by the ability to regenerate a fertile plant from the engineered cell through tissue culture. Here, we report that Wuschel2 (Wus2)-enabled transformation increases not only the transformation efficiency, but also the CRISPR/Cas-targeted genome editing frequency in sorghum (Sorghum bicolor L.). Using Agrobacterium-mediated transformation, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…Our observation that the expression level of Cas9 is indeed higher in pZKD673 transgenic plants than the pZKD672 transgenic plants confirmed our hypothesis. Very recently, another group also observed the same mutation efficiency increasement by co-expressing WUS in sorghum (Che et al, 2022), but the detailed mechanism hasn't been revealed. These works revealed the power of DRs, not only on genotype-independent genetic transformation, but also in efficient genome editing.…”
Section: Discussionmentioning
confidence: 97%
“…Our observation that the expression level of Cas9 is indeed higher in pZKD673 transgenic plants than the pZKD672 transgenic plants confirmed our hypothesis. Very recently, another group also observed the same mutation efficiency increasement by co-expressing WUS in sorghum (Che et al, 2022), but the detailed mechanism hasn't been revealed. These works revealed the power of DRs, not only on genotype-independent genetic transformation, but also in efficient genome editing.…”
Section: Discussionmentioning
confidence: 97%
“…The Agrobacterium-mediated QuickWheat transformation system uses a thymidine auxotrophic Agrobacterium strain (LBA4404 Thy-) harboring the ternary vector system with accessory plasmid pPHP71539 (pVir) for T-DNA delivery as described previously for maize (Anand et al, 2018) and sorghum (Che et al, 2018;Che et al, 2022) 2) to induce callus and rapid somatic embryo formation (Figure 1F, and G). Shoot regeneration and rooting was induced in the somatic embryos on culture medium #400 (Table 2) with selection (150 mg/L G418) to generate transgenic plantlets before transfer to soil.…”
Section: Non-excision Wheat Transformation Methodsmentioning
confidence: 99%
“…Recently, significant progress has been made toward more efficient wheat transformation with reduced genotype dependency and tissue culture cycle time by application of growth-regulating and regeneration related genes, such as TaWox5 (Wang et al, 2022) and the chimeric fusion Grf-Gif (Debernardi et al, 2020). In this study, we have taken advantage of the Zm-Baby Boom ( ZmBbm ) and Zm-Wuschel2 ( ZmWus2 ) mediated transformation technologies developed in maize ( Zea mays L.) (Lowe et al, 2016) and sorghum ( Sorghum bicolor L.) (Che et al, 2022). We extended those technologies to wheat and established two wheat transformation methods ( Figure 3B ) for generating high-quality events across multiple genotypes, either with or without morphogenic and marker gene excision (hereby referred to as the ‘QuickWheat’ transformation system).…”
Section: Introductionmentioning
confidence: 99%
“…Given that some morphogenic factors function in hierarchical order during embryogenesis and meristem formation (WANG et al 2020a;WU et al 2022), we reasoned that their combination may promote somatic embryogenesis in an additive manner, similar to the original BBM WUS2 system. We therefore tested whether the combination of the maize BBM gene (ZmBBM/EREB53) and the wheat GRF4-GIF1 chimera worked synergistically to enhance maize regeneration during Agrobacteriummediated embryo transformation, as previously hypothesized (DEBERNARDI et al 2020).…”
Section: The Ggb System For Maize Transformationmentioning
confidence: 99%
“…However, due to pleiotropic effects, removal of both morphogenic regulators from transgenic plants is required in this system (LOWE et al 2018;WANG et al 2020b). Alternative strategies have been pursued to obviate this issue (LOWE et al 2018;HOERSTER et al 2020;CHE et al 2022). Recently, when combined with Agrobacterium strains carrying a helper plasmid (an improved ternary vector carrying additional virulence genes), another member of WUSCHEL family, TaWOX5, was found to dramatically increase transformation efficiency of the maize inbred lines B73 and A188, generating transgenic plants without obvious developmental defects (WANG et al 2022b;WANG et al 2022a).…”
Section: Introductionmentioning
confidence: 99%